The Terrorist and his Jailor: The Conundrum of Friendship and Intimacy. Issue 1 (18th April 2018) - Ghosh, Durba
Abstract : Through the framework of "friendship" defined by Judith Butler, Leela Gandhi, and Vanessa Smith, this essay tracks the relationship between Trailokya Nath Chakrabarty, a Bengali revolutionary terrorist who spent three decades in British jails in colonial India and Francis Lowman, a police officer who was responsible for his imprisonment. Informed by Chakrabarty's autobiography, the essay shows that terrorism and intimacy were closely linked. Even though the revolutionary terrorist and jailor opposed one another in violent ways, these relationships were grounded in mutual recognition and built on what (following Butler) is called the "fundamental sociality of colonialism."